A house dividing : the Lincoln-Douglas debates of 1858 - Berry, Stephen William (Dialogues in history., 2016)
A House Dividing: The Lincoln-Douglas Debates of 1858 updates the Lincoln-Douglas debates for the sound-bite era. Instead of 100,000 words, this volume in the Dialogues in History series gives students 20,000 words from the debates. Rather than long, uncontested ramblings, it offers rapid-fire accusations and responses. Despite their reputations as intellectual heavyweights, Lincoln and Douglas were not above mudslinging; their arguments prove surprisingly studded with ad hominem attacks, political grandstanding, and gross appeals to the candidates' respective bases. Historians generally agree.